Moravian Cemeteries on Barbados: Sites of Historical, Social, and Political Change. (2nd September 2018) - Blouet, Helen
ABSTRACT: In the nineteenth century, African Moravians used Moravian church cemeteries on Barbados, and their use of such spaces was mediated by their situations in contexts of race, class, and religion. Mortuary practices from slavery to freedom represented social constraints as well as social freedom for individuals and communities. The extent to which we can explore through burials the history and development of mortuary practices in Moravian cemeteries is complicated by each cemetery's preservation and modification projects. Church cemeteries exist in varying degrees of stability, use, and disrepair. They may have been destroyed, as in the case of Bunker's Hill, or they may have been differentially preserved and modified as reflected in the Sharon, Mt. Tabor, Calvary, and Clifton Hill cemeteries. Through church cemetery care and analysis, it is possible to enhance awareness of historical complexity in African Moravian life and death on Barbados.